Heterologous Anti-Rabies Immunoglobulin - Results of the First Five Years of Production - E. G. Abramova; A. K. Nikiforov; O. A. Lobovikova; S. A. Eremin; Yu. G. Vasin; T. A. Mikheeva; I. M. Zhulidov; L. N. Minaeva; M. V. Galkina; L. V. Savitskaya; A. G. Selezneva; R. A. Svintsov; et al. (Проблемы особо опасных инфекций, 2010)
Presented are the comparative data of actual and regulated indicators of the qualitative characteristics of the heterologous anti-rabies immunoglobulin produced by the RARI Microbe for the five years of serial preparation manufacturing. Modern high-technology methods to control the baromembrane processes used in immunoglobulin purification are highlighted.